Third Grade Manatee Curriculum—Lesson 7: What Do Manatees Need to Survive? - Maia McGuire; Ruth Francis-Floyd (EDIS)
This 7-page fact sheet is the seventh lesson of the Third Grade Manatee Workbook series. This curriculum provides a series of individual lessons covering manatee biology and ecology, as well as highlighting some of the ways that humans impact and can protect manatees. The curriculum has been written at a third-grade level but can be adapted for older or younger students. Written by Ruth Francis-Floyd and Maia McGuire, and published by the Veterinary Medicine—Large Animal Clinical Sciences Department, UF/IFAS Extension, July 2015. (Photo credit: Keith Ramos, USFWS)